# Help with division? (steps please)

The equation is (x^6y^6-x^3y^3)/x^3y^3

How do I get to the answer?

The equation is (-16y^3+24y^4)/(-4y^2)

The equation is (-20a^2b+12ab^2)/(-4ab)

The equation is (3x^2y+6x^2y^2+3xy)/(3xy)

+1 vote
The equation is (x^6y^6 - x^3y^3)/x^3y^3

Distribute x^3y^3

(x^6y^6)/ x^3y^3 - (x^3y^3)/x^3y^3

Cacel common terms

(x^6y^6)/ x^3y^3 - 1

Recall a^m/a^n = a ^(m-n)

x^6/x^3 = x^(6-3) = x^3

y^6/y^3 = y^(6-3) = y^3

The equation is (-16y3+24y4)/(-4y2)

Distribute -4y2

= (-16y3)/ (-4y2) + (24y4)/(-4y2)

Cacel common terms

= 4y3/ y2 + (-6y4)/y2

Recall am/an = a (m-n)

y3/y2 = y(3-2)   = y

y4/y2 = y(4-2)   = y2

+1 vote

The equation is (-20a2b+12ab2)/(-4ab)

Distribute -4ab

= (-20a2b) / (-4ab) + (12ab2)/(-4ab)

Cacel common terms

= (5a2b) / ab) - (3ab2/ab)

Cancel common terms ab in numerator and denominator

Answer is     = 5a - 3b

+1 vote

The equation is (3x2y + 6x2y2 + 3xy ) / (3xy)

Distribute 3xy

=(3x2y/ 3xy) + (6x2y2 / 3xy) + (3xy/ 3xy)

Cancel common terms 3xy

= x + 2xy + 1